Studi Pengembangan Permukiman Berbasis Green City di Kecamatan Betoambari, Kota Baubau - Irsan Ely Kibas; Batara Surya; Jufriadi Jufriadi; Nani Anggraini (Fakultas Teknik Universitas Bosowa, 2023)
As time goes by, human needs increase with the human population growth in an area and provide quite real development impacts, both positive and negative impacts. One example of the adverse effects of development is environmental pollution that occurs as a result of human activities in it. Settlements are one of the human needs that grow rapidly over time. the need for housing in urban areas has recently begun to develop not only in the city center but has begun to show signs of growth in the suburbs. Betoambari District, Baubau City, which is the study area in this research, is one of them, Betoambari District, which is defined in the spatial planning document as a settlement development area. This is also supported by the carrying capacity and capacity of the land in Betoambari District, which can support activities including settlement activities. this research will find out the ability of Betoambari District in adopting the green city concept in development by testing several green city index test variables and providing input related to development with the green city concept as to what can be applied to prevent impacts due to development through an ecological approach by adopting the concept green city